2010
DOI: 10.1189/jlb.0310183
|View full text |Cite
|
Sign up to set email alerts
|

How specificity for self-peptides shapes the development and function of regulatory T cells

Abstract: The cataclysmic disease that develops in mice and humans lacking CD4+ T cells expressing the transcription factor Foxp3 has provided abundant evidence that Foxp3+CD4+ Tregs are required to suppress a latent autoreactivity of the immune system. There is also evidence for the existence of tissue-specific Tregs that can act to suppress regional autoimmune responses, suggesting that Tregs exert their effects, in part, through responding to self-peptides. However, how the immune system generates a repertoire of Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 61 publications
4
26
0
Order By: Relevance
“…IFN-c responses may reflect the absence of suitable T cells through depletion of the 5T4-specific helper response during development. Indeed, murine 5T4-specific transcripts were detected in the WT thymus providing for expression of this self-antigen and the capacity for negative deletion of high avidity self-reactive T cells and also the generation of specific natural Treg cells [38]. Hence, the differential ability to drive CD8 ?…”
Section: Discussionmentioning
confidence: 98%
“…IFN-c responses may reflect the absence of suitable T cells through depletion of the 5T4-specific helper response during development. Indeed, murine 5T4-specific transcripts were detected in the WT thymus providing for expression of this self-antigen and the capacity for negative deletion of high avidity self-reactive T cells and also the generation of specific natural Treg cells [38]. Hence, the differential ability to drive CD8 ?…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, we found that activated Treg populations exhibited a broad TCR-Vb pattern, implying that activation takes place in a polyclonal fashion. As the repertoire of human Tregs is shaped toward recognition of autoantigens, 36 LNs may serve as a place where Tregs interact with their cognate antigen. Support for this notion comes from a mouse study where a portion of naive CD4 pos T cells was found to interact with endogenous antigens in LNs, causing temporary expression of CD69 on these cells.…”
Section: Discussionmentioning
confidence: 99%
“…org/licenses/by-nc-sa/3.0/). development of Tregs expressing defined TCRs [4][5][6]. Among the self-proteins to which tolerance is acutely important for health and homeostasis, immunoglobulins (Ig) are unique.…”
Section: Are Treg Epitopes Present In Self-proteins?mentioning
confidence: 99%